2020
DOI: 10.1101/2020.11.12.379271
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ten-year projection of white-nose syndrome disease dynamics at the southern leading-edge of infection in North America

Abstract: Predicting the emergence and spread of infectious diseases is critical for effective conservation of biodiversity. White-nose syndrome (WNS), an emerging infectious disease of bats, has resulted in high mortality in eastern North America. Because the fungal causative agent Pseudogymnoascus destructans is constrained by temperature and humidity, spread dynamics may vary greatly by geography. Environmental conditions in the southern part of the continent, where disease dynamics are typically studied, making it d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…This conclusion is also corroborated by results obtained from disease dynamics modelling showing that environmental transmission is the primary infection mode in P . destructans (Meierhofer et al, 2021). Moreover, microbiome studies found similar fungal and bacterial assemblages on bat wings and hibernacula walls, reiterating the strong influence of site on the bat skin microbiome, which results in predominantly site‐specific microbiota (Ange‐Stark et al, 2019; Avena et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is also corroborated by results obtained from disease dynamics modelling showing that environmental transmission is the primary infection mode in P . destructans (Meierhofer et al, 2021). Moreover, microbiome studies found similar fungal and bacterial assemblages on bat wings and hibernacula walls, reiterating the strong influence of site on the bat skin microbiome, which results in predominantly site‐specific microbiota (Ange‐Stark et al, 2019; Avena et al, 2016).…”
Section: Discussionmentioning
confidence: 99%